In situ NAP-XPS spectroscopy during methane dry reforming on ZrO2/Pt(1 1 1) inverse model catalyst. (8th June 2018) - Rameshan, C; Li, H; Anic, K; Roiaz, M; Pramhaas, V; Rameshan, R; Blume, R; Hävecker, M; Knudsen, J; Knop-Gericke, A; Rupprechter, G
Abstract: Due to the need of sustainable energy sources, methane dry reforming is a useful reaction for conversion of the greenhouse gases CH4 and CO2 to synthesis gas (CO  +  H2 ). Syngas is the basis for a wide range of commodity chemicals and can be utilized for fuel production via Fischer–Tropsch synthesis. The current study focuses on spectroscopic investigations of the surface and reaction properties of a ZrO2 /Pt inverse model catalyst, i.e. ZrO2 particles (islands) grown on a Pt(1 1 1) single crystal, with emphasis on in situ near ambient pressure x-ray photoelectron spectroscopy (NAP-XPS) during MDR reaction. In comparison to technological systems, model catalysts facilitate characterization of the surface (oxidation) state, surface adsorbates, and the role of the metal-support interface. Using XPS and infrared reflection absorption spectroscopy we demonstrated that under reducing conditions (UHV or CH4 ) the ZrO2 particles transformed to an ultrathin ZrO2 film that started to cover (wet) the Pt surface in an SMSI-like fashion, paralleled by a decrease in surface/interface oxygen. In contrast, (more oxidizing) dry reforming conditions with a 1:1 ratio of CH4 and CO2 were stabilizing the ZrO2 particles on the model catalyst surface (or were even reversing the strong metal support interaction (SMSI) effect), as revealed by in situ XPS. Carbon deposits resulting from CH4 dissociation were easily removed by CO2 or by switching to dry reforming conditions (673–873 K). Thus, at these temperatures the active Pt surface remained free of carbon deposits, also preserving the ZrO2 /Pt interface.